2005
DOI: 10.1021/jo050625l
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies on Stevastelins. 1. Total Synthesis of Stevastelins B and B3

Abstract: [Chemical reaction: See text] The synthesis of stevastelin B3 (2) and B (5) are described. In a first approach, epoxy cyclodepsipeptide 8 was considered as a promising candidate for the synthesis of the [15]-membered ring members of the stevastelins; however, the oxirane ring opening, required for the completion of the natural stevastelin synthesis, failed. Thus, we synthesized stevastelin B (5), carrying out the oxirane ring opening earlier in the synthesis and following a synthetic scheme capable of deliveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Another fraction consisting of a 4/1 mixture of amphidinolides J and R was also isolated (15%). Interestingly, under similar conditions (rt, 4 h), an acyl shift took place from the 14-membered lactone 25 and amphidinolide J was again isolated as the major product (46%) along with a 1/1 mixture of amphidinolides J and R (18%) (Scheme ). , The spectroscopic data of the isolated pure amphidinolide J were in perfect agreement with those previously reported for the natural product (Δδ ≤ 0.1 ppm in 1 H and 13 C NMR) with a measured optical rotation slightly higher ([α] D +6.7 ( c 0.52, MeOH); lit [α] D +1.2 ( c 0.7, MeOH)).…”
supporting
confidence: 85%
“…Another fraction consisting of a 4/1 mixture of amphidinolides J and R was also isolated (15%). Interestingly, under similar conditions (rt, 4 h), an acyl shift took place from the 14-membered lactone 25 and amphidinolide J was again isolated as the major product (46%) along with a 1/1 mixture of amphidinolides J and R (18%) (Scheme ). , The spectroscopic data of the isolated pure amphidinolide J were in perfect agreement with those previously reported for the natural product (Δδ ≤ 0.1 ppm in 1 H and 13 C NMR) with a measured optical rotation slightly higher ([α] D +6.7 ( c 0.52, MeOH); lit [α] D +1.2 ( c 0.7, MeOH)).…”
supporting
confidence: 85%
“…Installation of the C-2/C-3 syn aldol moiety was achieved using Evans syn aldol condensation (Scheme ), giving 40 in 94% yield. The chiral auxiliary was then removed by reduction with LiBH 4 . The resulting diol 41 was selectively silylated with TBDPSCl at the primary OH to afford 42 .…”
Section: Resultsmentioning
confidence: 99%
“…xvi Sandoval et al, reported that (R)-3-hydroxy-n-phenylalkanoic acid had a significant antimicrobial effect against food pathogen such as Listeria monocytogenes present in the refrigerated food [33]. (R)-3-hydroxy-undecanoate is utilized for synthesis of depsipeptides (antibiotic/antifungal) [34]; lipid A mimic (immunobiological) [35]; (−)-tetrahydrolipstatin (antiobesity drug) [36]. (R)-3-hydroxyhexanoate is used for production of anti-microtubule agent such as analogs of laulimalide [37].…”
Section: Siv 231 Synthesis Of Chiral Compounds and Drugsmentioning
confidence: 99%